2014
DOI: 10.1177/0954405414555590
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of friction welding parameters in AISI 304L austenitic stainless steel and copper joints

Abstract: Friction welding is a solid-state joining technique, and joining of dissimilar materials has been witnessing tremendous development in various applications. In this study, friction welding is carried out in dissimilar materials, austenitic stainless steel and copper, which find application in power generators. The parameters such as friction pressure, upset pressure, rotational speed and burn-off length are considered to determine its influence on tensile strength, metal loss and weld time. Taguchi’s L27 ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…Copper-SS joints have been produced by using various solid state or fusion welding processes. Solid state welding processes like diffusion welding, friction stir welding (FSW), and explosive welding have been extensively used [3][4][5][6][7][8]. In diffusion welding of copper-SS, the interlayer material, applied temperature, and pressure, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper-SS joints have been produced by using various solid state or fusion welding processes. Solid state welding processes like diffusion welding, friction stir welding (FSW), and explosive welding have been extensively used [3][4][5][6][7][8]. In diffusion welding of copper-SS, the interlayer material, applied temperature, and pressure, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Imani et al [7] for FSW of copper-SS joints reported that off-setting of the pin toward copper side by 30% produced defect free welds with better tensile strength. Shanjeevi et al 2016 [8] reported that friction pressure is the most significant process parameter of FSW followed by pin rotational speed affecting the resultant microstructure and tensile properties of copper-SS joints. For fusion welding of copper-SS, different arc welding processes and high energy density Laser Beam Welding (LBW) or Electron Beam Welding (EBW) processes have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the effectiveness of the models for Hardness, Impact strength and Tensile strength responses performed by the help of R 2 (coefficient of determination, R 2 ) values. R 2 (Coefficient of determination) is used to check the goodness of the model; it determines how close the predicted values with the experimental values [36,[41][42][43][44]. When R 2 approaches to the value of 1, implying the response models have closely resembled the actual (experimental) data.…”
Section: R-testmentioning
confidence: 99%
“…1., shows the uniform distribution of the composite particles in the metal matrix aluminium alloy AA7075 + 10 % vol SiCP-T6. Friction welding on the cast rods of AA7075 + 10 % vol SiCP-T6 had been done on the continues drive friction welding using the Taguchi's L27 orthogonal array framed by taking the four process parameters such SS, FP, UP and BOL with three level in each of them [11] as shown in the Table 2. The samples were then friction welded as per the Taguchi's L27 orthogonal array shown in the Table 3.…”
Section: Materials Preparation and Friction Weldingmentioning
confidence: 99%